Design and Development of College Student Worksheets for Simulation of Electromagnetic Waves - Marlinda Siahaan; Betty Zelda Siahaan (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
Many studies show that student worksheets can be suitable teaching materials to achieve learning objectives, whether at school or college. Also, college student worksheets can make it easier for students to learn computing-based lessons. This study aims to design and develop worksheets and integrate them with computational thinking (CT) skills in computer programming courses. The material intended to be used as a worksheet is how to simulate electromagnetic waves (EM). This worksheet is also designed with group activities and is expected to improve collaboration skills between college students. This study uses research and development (R&D) methods with the 4D model approach but does not do the fourth stage, dissemination. The worksheet developed has six main elements: (1) titles, (2) study guides, (3) essential competencies, (4) subject matter or supporting information, (5) tasks or work steps, and (6) student assessments. The resulting worksheet products have also been assessed by peers and declared worthy as teaching materials. In addition, the resulting worksheet has shown the steps in CT, namely, abstraction, algorithm, and generalization.